„Muł na to zrobiony, żeby nosił księży i podróżnych uczonych”. Wizerunek zwierząt we "Wspomnieniach z podróży" Teodora Tripplina - Gintowt, Aleksandra (2022)
In this paper the author analyses Teodor Tripplin’s Wspomnienia z podrózy from the perspective of animal studies.The book is a travel memoir containing elements of fiction and it was published in the 19th century. Beginning withan introduction to the situation of animals in that time, the author of the article moves away from the protagonistand his human companions and instead focuses on their perception of the animals they encounter while travelingacross European and African countries. There is a clear division between those animals that are close to humans,classified as ‘intelligent’ (like dogs), and wild animals, which are divided into four categories: food, fur, entertainmentand danger. The author often attributes human characteristics to dangerous animals in order to ‘prove’ their realnature to the reader. Wild animals should be killed or tamed, while the purpose of companion animals establishestheir usefulness to humans. There are tropes of speciesism and examples of the use of animals, not only in practice(physical labor) but also in symbolism and language, including stereotypically common terms and phraseologicalpatterns. The purpose of this article is to analyze Tripplin’s works in order to illustrate how the traveler viewed anddescribed animals and how this relates to the history of the formation of animal rights.
Keywords: Tripplin, Teodor